"Such business will be impossible": Mitsubishi Trading Company and the roles of design and tariff policy in the American bicycle market (1933–1938). Issue 1 (June 2021) - Longhurst, James
During the 1930s Mitsubishi Shoji Kaisha, a Japanese trading conglomerate, attempted to foster a market for adult bicycles in America. They promoted bikes manufactured by Nichibei Shoten (including Fuji, a brand eventually known worldwide). These imported designs were rare for the American market, reflecting European and Japanese use of the bicycle as urban transportation for adults, instead of American predilections for bicycles designed for children's recreation. If Mitsubishi had been successful – introducing designs for adult practical bicycling that existed in other markets worldwide – mobility in the United States might be different today. But these possibilities were precluded by steep tariff walls, a legacy of xenophobic protectionism, and (eventually) global war. During the war the federal government seized Mitsubishi's records, which now afford a rare opportunity to explore the divergences between worldwide transportation cultures, and to understand how policies structuring the global flow of goods shape local mobilities.